Spectrum of Optic Disc Edema with Macular Star and Neuroretinitis – A Literature Review - Snehanka Ganpat Parab; Saroj Indersain Sahdev (Delhi Journal of Ophthalmology)
Neuroretinitis (NR) is a condition characterized by the fundus appearance of optic disc edema and subsequent formation of a macular star figure. What we commonly referred to as NR is now identified to be a clinical presentation in a variety of disorders having both infectious and noninfectious etiologies. The descriptive term optic disc edema with a macular star (ODEMS) better encompasses this heterogeneous group of disorders. During clinics, the ambiguity surrounding terminology, varied presentations, and lacunae in literature prompted us to do this research. We searched through databases such as Google Scholar, PubMed, and directory of open access journals using keywords NR optic disc edema with macular star (ODEMS), cat scratch disease, and selected the high impact original journal articles and review since 1950. The clinical diagnosis is a challenge because these diseases share similar if not identical clinical presentation and laboratory support is often indispensable. The purpose of this review is to provide an approach to a patient having optic disc edema with macular star or ODEMS and NR based on the current understanding of the entity and bring about a consensus regarding its nomenclature.